PARADIGMA E-DIPLOMACY: FORMULASI KEBIJAKAN PENGEMBANGAN SOFT POWER DIPLOMACY - Tri Darmawan Adimihardja; Gunawan Undang; Tom Finaldin (Hubungan Internasional, 2022)
Along with the industrial revolution (IR) 4.0, digital diplomacy or e-diplomacy is a necessity. However, these studies are still not widely developed. This article attempts to explain it – albeit with a very limited scope – from a public policy perspective. By using descriptive-qualitative method, the data source of this study was obtained from literature study. The results of the study show that e-diplomacy 4.0 is one part of the discipline of international relations, especially soft power diplomacy. After entering the early phase of society 5.0, diplomacy study actors have the opportunity to be more open to combining the two. Thus, a new paradigm is needed as the development of a conceptual framework for the study of international relations that develops in a multidisciplinary manner. The contribution of this article is the Paradigm Conceptual Framework of E-Diplomacy 4.0 and Society 5.0 as an effort towards e-diplomacy policy formulation. Through this paradigm, it is hoped that it will have implications for policy formulation efforts – by the government as a public policy actor – so that the participation and innovation of public soft power diplomacy in the digital field is more developed.Keywords: e-diplomacy paradigm – policy formulation – soft diplomacy